OPTIMALISASI MUTU KRISAN POT DENGAN BENIH VARIETAS KRISAN POTONG MENGGUNAKAN ZAT PENGATUR TUMBUH PACLOBUTRAZOL DAN DAMINOZIDE - E. Dwi Sulistya Nugroho; Ardian Elonard (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTThe purpose of this study was to obtain the concentration and frequency of giving the right plant growth regulator to produce compact chrysanthemum pot with a lot of flower production and good quality plants and flowers by using chrysanthemum cut flowers as seeds. The research was designed using a Randomized Block Design consisting of two factors. The first factor is a plant growth regulator concentration consisting of 10 ppm paclobutrazol, 20 ppm paclobutrazaol, 30 ppm paclobutrazol, 40 ppm paclobutrazol, 40 ppm paclobutrazol, 50 ppm, daminozide 2500 ppm, daminozide 5000 ppm. The second factor is the frequency of plant growth regulator consisting of three levels, namely one time giving, two times giving and three times giving. The results showed the higher the concentration of plant growth regulator andthe frequency of plant growth regulator, accordingly reduced the plant height, number of flower stalks, number of flower buds, flower bud diameter and plant crown diameter. Application of Paclobutrazol 10 ppm with one time giving a moresimultaneously and compact plant height compared to the use of 2500 ppmDaminozide, although the production of flower stalks and fewer buds.